Respiration-induced B0 field fluctuation compensation in balanced SSFP: real-time approach for transition-band SSFP fMRI. - Lee, J; Santos, J; Conolly, S; Miller, K; Hargreaves, B; Pauly, J (2006)
In functional MRI (fMRI) the resonance frequency shift induced from respiration is a major source of physiological noise. In transition-band SSFP fMRI the respiration-induced resonance offset not only increases noise interference, it also shifts the activation band. This leads to a reduction in the contrast-to-noise ratio (CNR) and the potential for varying contrast levels during the experiment. A novel real-time method that compensates for the respiration-induced resonance offset frequency is presented. This method utilizes free induction decay (FID) phase information to measure the resonance offset. For compensation, one can update the resonant frequency in real time by changing the transmit RF pulse and receiver phases to track the measured offset. The results show decreased signal power in the respiration frequency band and increased numbers of activated voxels with higher Z-scores compared to uncompensated experiments.